Effects of Gamma Irradiation on Mating Competitiveness of Male Culex quinquefasciatus (Diptera:Culicidae) in Laboratory - T. Ramadhani; U.K. Hadi; S. Soviana; Z. Irawati; A. Rahayu; S Sunaryo (PPIKSN-BATAN, 2020)
Culex quinquefasciatus is the main vector of lymphatic filariasis in Pekalongan City. Sterile Insect Technique (SIT) can be employed as complementary vector control for filariasis. The key success of this technique depends on the ability of laboratory-reared sterile males to mate with the wild-type females. This research aimed to was to determine the mating competitiveness, fecundity and fertility of sterile males of Cx. quinquefasciatus. The pupae of Cx. quinquefasciatus were gamma irradiated at doses of 60, 70, and 80 Gy, whereas unirradiated pupae were prepared as control. The mosquitoes emerging from the irradiated pupae were found to be able to mate with normal females in the cages. Observation was done for the mean female laying eggs, the fecundity, the fertility and the mating competitiveness. The observation data were analyzed by one-way ANOVA. The results show that the irradiated Cx. quinquefasciatus at the test doses does not affect the fecundity and the mating competitiveness, but the fertility is disturbed (sterile). A dose of 70 Gy was found to be the optimum dose, which gave a fertility rate of 1.8 % (98.2 % sterile) with a value of competitiveness (C index) of 0.568. Based on these results, irradiated Cx. quinquefasciatus can be recommended for semifield application.